2021
DOI: 10.22605/rrh6122
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring contact: calling rural Appalachian older adults during the COVID-19 epidemic

Abstract: Introduction: Older adults, especially those aged 85 years or older, remain at significantly higher risk for COVID-19. This group, along with those with pre-existing heart and lung disease and diabetes, have accounted for 80% of hospitalizations and an even higher percentage of COVID-19 related deaths in the USA. West Virginia, the only state in the USA located completely within Appalachia, has a higher percentage of elderly than all but two states in the nation. Rural seniors are hesitant to use hospital emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In concordance with previous literature (Ministère de la Santé Preventive measures leading to cancelling home services (Ito et al, 2021) Most adaptations to the COVID-19 pandemic required a reliable Internet service (Beckman, 2021;Joseph et al, 2021;Tremmel, 2020). People with less access to the technological device and less knowledge on how to use the Internet may be excluded from these services despite often being those who most need them (Beckman, 2021;Shapira, 2021;Walker et al, 2021) Technological difficulties (Quinn et al, 2020) Living alone is associated with psychological outcomes such as anxiety, depression and overall decreased well-being (Goodman-Casanova et al, 2020;Walker et al, 2021) Lower socio-economic status, geographic isolation and overall marginalisation was a barrier to access services (Beckman, 2021;Shapira, 2021;Tremmel, 2020) Change in the resource and services modality could affect their content (Lai et al, 2020) Privacy concerns when using video calls were reported (Scheffers, 2021) Decrease the quality of the communication (e.g. lack of nonverbal signals; Scheffers, 2021) Relying too much on informal caregivers can lead to an increased burden or burnout (Franzosa et al, 2020;Sadarangani et al, 2021)…”
Section: Included Sourcessupporting
confidence: 74%
See 3 more Smart Citations
“…In concordance with previous literature (Ministère de la Santé Preventive measures leading to cancelling home services (Ito et al, 2021) Most adaptations to the COVID-19 pandemic required a reliable Internet service (Beckman, 2021;Joseph et al, 2021;Tremmel, 2020). People with less access to the technological device and less knowledge on how to use the Internet may be excluded from these services despite often being those who most need them (Beckman, 2021;Shapira, 2021;Walker et al, 2021) Technological difficulties (Quinn et al, 2020) Living alone is associated with psychological outcomes such as anxiety, depression and overall decreased well-being (Goodman-Casanova et al, 2020;Walker et al, 2021) Lower socio-economic status, geographic isolation and overall marginalisation was a barrier to access services (Beckman, 2021;Shapira, 2021;Tremmel, 2020) Change in the resource and services modality could affect their content (Lai et al, 2020) Privacy concerns when using video calls were reported (Scheffers, 2021) Decrease the quality of the communication (e.g. lack of nonverbal signals; Scheffers, 2021) Relying too much on informal caregivers can lead to an increased burden or burnout (Franzosa et al, 2020;Sadarangani et al, 2021)…”
Section: Included Sourcessupporting
confidence: 74%
“…The professionals interviewed in one study expressed their concerns specifically about reaching vulnerable older adults (Beckman, 2021). On the contrary, three studies (33.3%) reported an equivalent delivery of services before and during the pandemic despite having to adapt to sanitary measures (McKenzie et al, 2021; Tremmel, 2020; Walker et al, 2021). All these studies focused on municipality or government organisations; two provided education services to individuals with disabilities and the other one delivered health prevention services.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, non-Hispanic Black persons were more likely to report they had received a checkup from a doctor in the past 12 months (93.8%) compared to non-Hispanic White persons (89.2%) ( 19 ). When considering the additional impact of COVID-19, economic hardship, co-morbidities, and challenges with visiting health care providers (e.g., shuttered doors, fear of contracting COVID, telehealth inconsistencies, etc…) worsened access to care for older adults, particularly African Americans, and persons with geographic barriers that made getting to the doctor difficult ( 15 , 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%